Prognostic impact of peripheral natural killer cells in primary central nervous system lymphoma - Lin, Zhiguang; Ma, Jingjing; Ma, Yan; Li, Qing; Kang, Hui; Zhang, Mengxue; Chen, Bobin; Xia, Rong (Frontiers in Immunology, 2023)
Background Primary central nervous system lymphoma (PCNSL) is an aggressive extranodal non-Hodgkin lymphoma with a poor prognosis. We aimed to evaluate the prognostic impact of circulating NK cells in PCNSL. Materials and methods Patients diagnosed with PCNSL who were treated at our institution between December 2018 and December 2019 were retrospectively screened. Patient variables including age, sex, Karnofsky performance status, diagnostic methods, location of lesions, lactate dehydrogenase, cerebrospinal fluids (CSF), and vitreous fluids involvement or not were documented. NK cell count and NK cell proportion (NK cell count/lymphocyte count) in the peripheral blood were evaluated by flow cytometry. Some patients underwent two consecutive NK cell tests before and three weeks after chemotherapy (before the next chemotherapy). The fold change in NK cell proportion and NK cell counts were calculated. CD56-positive NK cells in tumor tissue were assessed by immunohistochemistry. NK cell cytotoxicity assay was performed using flow cytometry. Results A total of 161 patients with PCNSL were included in this study. The median NK cell count of all NK cell tests was 197.73/μL (range 13.11–1889.90 cells/μL). The median proportion of NK cells was 14.11% (range 1.68–45.15%) for all. Responders had a higher median NK cell count (p<0.0001) and NK cell proportion (p<0.0001) than non-responders. Furthermore, Responders had a higher median fold change in NK cell proportion than non-responders (p=0.019) or patients in complete remission/partial remission (p<0.0001). A higher median fold change in NK cell count was observed in responders than in non-responders (p=0.0224) or patients in complete remission/partial remission (p=0.0002). For newly diagnosed PCNSL, patients with a high NK cell count (>165 cells/μL) appeared to have a longer median overall survival than those with a low NK cell count (p=0.0054). A high fold change in the proportion of NK cells (>0.1957; p=0.0367) or NK cell count (>0.1045; p=0.0356) was associated with longer progression-free survival. Circulating NK cells from newly-diagnosed PCNSL demonstrated an impaired cytotoxicity capacity compared to those from patients with PCNSL in complete remission or healthy donors. Conclusion Our study indicated that circulating NK cells had some impact on the outcome of PCNSL.